IMPACT OF THE EMISSIONS FROM A PLANT OF THERMALLY INSULATING MATERIALS ON PUBLIC HEALTH - Кислицына, Вера Викторовна; Суржиков, Дмитрий Вячеславович; Голиков, Роман Анатольевич; Ликонцева, Юлия Сергеевна; Мотуз, Ирэна Юрьевна (Medicine in Kuzbass, 2025)
The study aim was to assess the health risk to the population exposed to the emissions from a thermally insulating materials plant located in the city of Novokuznetsk. Materials and methods. The study was conducted at Izolit-NK LLC. The source of initial data was the volume of maximum permissible emissions of the enterprise. Calculations of maximum and average concentrations of pollutants in 40 points were performed using the ECOcenter-Standard software package in accordance with the Methods for calculating the dispersion of emissions of harmful (polluting) substances in the atmospheric air. Maximum permissible concentrations of substances were determined in accordance with the Sanitary Rules and Norms 1.2.3.3685-21. Risk calculations were performed using the Guideline 2.1.10.3968-23. Results. Nitrogen dioxide, nitrogen oxide, sulfur dioxide, carbon monoxide, benz(a)pyrene, phenol, formaldehyde and inorganic dust with SiO2 content of 20-70% were selected for non-carcinogenic risk assessment. Carcinogenic risk evaluation was performed for the exposure to benz(a)pyrene and formaldehyde. Maximum concentrations of pollutants range from 1.87 × 10-5 mg/m3 for formaldehyde to 0.097 mg/m3 for inorganic dust with SiO2 content of 20-70%. Average concentrations of pollutants range from 8.61 × 10-14 mg/m3 for benz(a)pyrene to 0.007 mg/m3 for carbon monoxide. No excesses of maximum permissible concentrations of the substances were detected. Non-carcinogenic risk in acute and chronic inhalation exposures corresponds to the minimum or permissible level. The total individual carcinogenic risk varies from 6.45 × 10-9 to 4.26 × 10-7, corresponding to the minimum level. Formaldehyde has the main specific gravity in the formation of carcinogenic risk. Conclusion. The calculated values of non-carcinogenic and individual carcinogenic risks caused by the impact of atmospheric emissions of Izolit-NK LLC correspond to the minimum or acceptable level. Therefore, the activities of the studied enterprise do not have a significant impact on the health of the population of Novokuznetsk.